Evaluation of cellular interactions with functionalized scaffolds for cardiovascular tissue engineering - Wimberley, Olivia (Division of General Surgery, 2022)
Introduction: Cardiovascular disease is a leading cause of death worldwide, with heart valve disease in particular becoming a rising problem in developing countries. Tissue engineering offers the next step in heart valve tissue replacement surgery. Synthetic scaffolds used in tissue engineering often do not have sufficient cell adhesion, thus the addition of biosignals is crucial. Surface modifications can be used to improve desired cell adhesion and proliferation. To covalently attach cell adhesion peptides/biosignals, synthetic hydrogel spacers are often used in an interim grafting step. Poly (acrylic acid) (PAA) is a non-toxic, FDA approved hydrogel that has been shown in preliminary studies (previous research and own experience) to improve cell adhesion even without the addition of specific cell-binding compounds. This project aims to show the effect of systematically increasing the concentration of PAA modified 2D and 3D polyurethanes (biodegradable and biostable) on cell adhesion, persistence, and proliferation. Experimental Methods: In Part 1, 2D nondegradable Pellethane® films were surface modified by varying the poly (acrylic acid-co-acrylamide) (P(AA-co-AM)) comonomer feed ratio from 0 to 100 % PAA in 20 % increments, using poly (acrylamide) (PAM) as a copolymer (unmodified and collagen coated controls). Surface properties were analysed using SEM imaging, staining, energy-dispersive X-ray spectrometry (SEM-EDS) and toluidine blue carboxyl assays (TBCA). Endothelial cells were isolated from human saphenous veins using an enzymatic digestion method, and identified by staining with DAPI and Cy3 against CD31. Isolated endothelial cells and human dermal fibroblasts (Cell bank: R039/2016) were seeded onto Pellethane® films (8 000 cells/film). Live/dead staining and XTT cell viability assays were performed over 24 and 72 hrs, respectively. Following this, XTT cell viability assays were performed at 7 and 24 hrs post-seeding on endothelial cells cultured under serum-free conditions (20 000 cells/film; unmodified and 80 % PAA). In Part 2, both Pellethane® and DegraPol® (degradable) 2D films and 3D electrospun scaffolds were used. The polymer samples were surface modified with 0, 40, and 80 % PAA. All samples were imaged using SEM prior to in vitro cell culture evaluation. Endothelial cells were seeded (8 000 cells/film) onto surface modified polymer samples, and XTT cell viability assays were performed over 72 hrs. Three-dimensional scaffolds seeded with endothelial cells (20 000 and 50 000 cells/film; unmodified and 80 % PAA) were immunocytochemically stained (Hoechst and CD31) at Day 1, 3, and 7 post-seeding. Results and discussion: In Part 1, SEM imaging and preliminary staining confirmed the addition of PAA to polymer surfaces. Systematically increasing [AA] in the P(AA-co-AM) comonomer ratio resulted in the expected increase in surface-COOH functional groups (TBCA and SEM-EDS). The number of COOH groups increased as [PAA] increased from 0-40 % (R 2=0.76; P 0.0001) before plateauing (TBCA). This was further confirmed by a decreasing N/O ratio with increasing [AA] monomer (R2=0.70; P< 0.001) (SEM-EDS). An increase in [PAA] resulted in a linear increase in endothelial cell adhesion and persistence (R 2=0.92 (live/dead staining) and 0.96 (XTT cell viability assays); P< 0.05). Endothelial cell viability on surfaces modified with 80 and 100 % PAA was comparable to that achieved on the collagen positive control. High concentrations of PAA also showed improved fibroblast adhesion (R2= 0.71 (live/dead staining) and 0.54 (XTT cell viability assays); P< 0.05) but did not display any persistence or viability close to that obtained on the collagen. Collagen coated surfaces displayed the highest cell adhesion and proliferation for both cell types (XTT cell viability assays and live/dead staining). Endothelial cell adhesion was improved by both the addition of PAA to the polymer surface, and FBS to the cell culture medium (P< 0.05) (cells cultured under serum-free conditions). In Part 2, the improvement of endothelial cell adhesion on PAA modified 2D Pellethane® films was confirmed and additionally shown on 2D DegraPol® (P ≤0.05) (XTT cell viability assays). However, the endothelial cell persistence seen in earlier assays was not observed. The positive effect of increasing [PAA] did not translate to 3D scaffolds, and cell behaviour was improved on unmodified surfaces in comparison to any of the PAA modified groups (XTT cell viability assays and immunocytochemical staining). This discrepancy is proposed to be a difference in grafting efficiency on the degradable materials and the 3D structure of the electrospun scaffolds. Conclusions: An increase in PAA surface modification on polyurethane can improve endothelial cell adhesion and persistence on nondegradable 2D polyurethane scaffolds. These results did not translate to electrospun scaffolds, probably due to the complex 3D cell environment. Further investigation is required for use in TEHV and other applications.